Configuration and Dynamics of the Laurentide Ice Sheet During the Late Wisconsin Maximum - Dyke, Arthur; Dredge, Lynda; Vincent, Jean-Serge (Géographie physique et Quaternaire)

(untitled) (Les Presses de l'Université de Montréal, 1982)
ABSTRACTPrior to 1943 the Laurentide Ice Sheet was considered to have three major domes centered in Keewatin, Labrador, and Patricia (TYRRELL, 1898 a, b; 1913). FLINT (1943) argued that these centres were of only local and temporary importance and favoured a single-domed ice sheet. Despite the lack of supporting geological evidence, and despite the proposition of a Foxe Dome in the interim (IVES and ANDREWS, 1963), the single-dome concept was not seriously challenged until the late 1970's and, in fact, is still strenuously supported (HUGHES era/., 1977 ; DENTON and HUGHES, 1981). This paper extends and modifies recent conclusions that the Laurentide Ice Sheet had more than one dome at the Late Wisconsin maximum. We propose a model incorporating five domes (M'Clintock, Foxe, Labrador, Hudson, and (?) Caribou) based on the position of ice divides, ice flow patterns, drift composition, late-glacial features, postglacial isostatic recovery and free-air gravity anomalies. Our Labrador and Hudson domes closely correspond to Tyrrell's Labradorean and Patrician ice sheets; our Caribou and M'Clintock domes together with the Franklin Ice Complex over the Queen Elizabeth Islands north of the Laurentide Ice Sheet, correspond to Tyrrell's original Keewatin Ice Sheet. The style of glaciation of the Foxe Basin region was not known to Tyrrell, but our reconstruction of the Foxe Dome is in close agreement with the original proposal of Ives and Andrews. Like Tyrrell, our reconstruction is based on field evidence obtained through extensive mapping; the single dome model continues to be unsupported by geological data.